Microlearning Video with Kata Kolok Sign Language Translation for Elementary Science Terminology: Matter and Its Changes - Ni Kadek Dwi Martini; Putu Nanci Riastini; Gusti Ayu Putu Sukma Trisna (MIMBAR PGSD Undiksha, 2024)
Science learning often uses scientific terms that are unfamiliar to students, causing misconceptions about students' understanding. This is also experienced by deaf students, due to the limitations of students communicating verbally. This development research aims to produce learning media in the form of microlearning videos, sign language translations, kolok words for elementary school science terminology, the topic of substance forms and their changes. Microlearning is selected according to the characteristics of inclusion students. This study uses the ADDIE Model. The subjects of this research trial consisted of 2 material and media experts. The results of this study were then analyzed using quantitative and qualitative descriptive techniques. The results of the validity test obtained a very high category, from material experts a score of 0.88 and a validity test by learning media experts obtained a score of 0.95. The feasibility of the media was also assessed from the response of teachers who obtained a score of 99% with very good qualifications and the student response test obtained a score of 89% with very good qualifications. Based on these results, it was stated that the media developed was feasible and practical to be used in science learning in inclusion classes. The implication of this study is that video microlearning can be used as an additional learning resource in science learning in inclusive classes on an ongoing basis.